(untitled) - Weinbach, Robert W
Includes bibliographical references and index.; Defining and describing management -- The context of human services management -- Historical origins of current approaches to management -- Planning -- Creating and managing staff diversity -- Promoting a productive work environment -- Staff performance evaluations and personnel actions -- Organizing -- Controlling -- Leading -- Other important management tasks -- Becoming an effective manager.; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Social work administration -- United States; Quản trị công tác xã hội -- Mỹ (Hoa Kỳ)